Inheriting a canoe paddle : the canoe in discourses of English-Canadian nationalism - Dean, Misao (Cultural spaces., 2013)
"If the canoe is a symbol of Canada, what kind of Canada does it symbolize? Inheriting a Canoe Paddlenbsp;looks at how the canoe has come to symbolize love of Canada for non-aboriginal Canadians and provides a critique of this identification's unintended consequences for First Nations. Written with an engaging, personal style, it is both a scholarly examination and a personal reflection, delving into representations of canoes and canoeing in museum displays, historical re-enactments, travel narratives, the history of wilderness expeditions, artwork, film, and popular literature. Misao Dean opens the book with the story of inheriting her father's canoe paddle and goes on to explore the canoe paddle as a national symbol -- integral to historical tales of exploration and trade, central to Pierre Trudeau's patriotism, and unique to Canadians wanting to distance themselves from British and American national myths. Throughout, Inheriting a Canoe Paddle emphasizes the importance of self-consciously evaluating the meaning we give to canoes as objects and to canoeing as an activity"--